Synthesis and Properties of Nitrogen-Containing Curved Heterosuperbenzene - Shi, Yubai; Li, Cheng; Ma, Shaohua; Zhang, Yin (Synthesis, 2018)
A novel nitrogen-functionalized curved superbenzene was prepared via oxidative cyclodehydrogenation of a suitable hexaarylbenzene precursor under mild conditions. The spectroscopic and electrochemical properties are detailed here and compared with those of permethoxylated hexa-peri-hexabenzocoronene. The crystal structure analysis confirmed that the molecule has an unequal ‘double-concave’ aromatic core due to the inclusion of a pyrimidine subunit and the steric encumbrance of the methoxy groups at the periphery.
Keywords: polycyclic aromatic hydrocarbons; double-concave; heterosuperbenzene; hexa-peri-hexabenzocoronene; cyclodehydrogenation